Role of Pretreatment Pan-Immune Inflammation Value as Predictive Marker of Response to Neoadjuvant Therapy in Locally Advanced Rectal Cancer: A Prospective Observational Study in a Tertiary Cancer Center - Lokesh, KN; Yaman, Patidar; Darshan, R.S.; AH, Rudresh; Rajeev, L.K.; Saldanha, Smitha C.; Giri, G.V.; MC, Suresh Babu (Indian Journal of Medical and Paediatric Oncology, 2025)
Neoadjuvant treatment in locally advanced rectal cancer (LARC) led to downstaging in nearly 50 to 60% of patients and pathological complete response (pCR) rates in 9 to 30% cases. However, cases not responding to neoadjuvant treatment encounter either a delay in definitive treatment or progression.To evaluate the role of pan-immune inflammation value (PIV) as a predictive marker of response to neoadjuvant therapy in LARC.A prospective observational study was conducted to validate the predictive value of response to pretreatment PIV in patients with LARC.One hundred twenty patients were enrolled in the study. Patients with higher PIV values were found to have poorer radiological response as compared with patients with lower values (55.1 vs. 75.8%, p = 0.045). Also, patients with high micro-satellite instability status had poor responses. pCR was seen in 21 patients (19.6%). Patients with high PIV value had a pCR rate of 11.6% as compared with 34.0% in the low PIV group.Pretreatment PIV value appears to be a predictive marker of response to neoadjuvant treatment in LARC.
Keywords: pan-immune inflammation value; rectal neoplasm; pathologic complete response; neoadjuvant therapy